(untitled) (Forum Penelitian Agro Ekonomi, 2019)
Price changes affect all aspects of agricultural activities, especially on agricultural development.To increase the production of strategic commodities such as rice, maize, and soybean, needs special attention to the impact of price changes closely related to that trading, so it is expected that the implications for farming income will be better and can make farmers more prosperous in the future. Often the fact, the growth in food demand is faster than the growth of its supply, causing changes in the price of staple foodstuffs, and ultimately impacting at the farmers income whose are uncertain. This paper aims to analyze the impact of changes in rice,maize and soybean prices on that trading, and its implications for farm income. The determination of the Reference Price of Purchase which only considers the cost of farming to produce rice, corn and soybean has not provided optimal support for efforts to increase the income of pajale farming. Therefore, it is necessary to consider all cost components, as well as government intervention in helping to strengthen the bargaining position of farmers in the trading system of these three commodities in Indonesia, so that the supply chain from farmers to the hands of end consumers can be cut, in order to provide direct implications for increased farm revenues. Abstrak Perubahan harga memengaruhi seluruh aspek kegiatan pertanian, khususnya terhadap pembangunan pertanian. Untuk meningkatkan produksi komoditas pangan utama, seperti padi, jagung, dan kedelai diperlukan perhatian khusus terhadap dampak perubahan harga yang berkaitan erat dengan perdagangannya sehingga diharapkan pendapatan usaha tani menjadi lebih baik dan petani makin sejahtera kedepannya. Seringkali faktanya bahwa pertumbuhan permintaan pangan lebih cepat dari pertumbuhan penyediaannya yang menyebabkan perubahan harga pangan pokok sering bergejolak dan akhirnya berdampak pada pendapatan petani yang tidak menentu. Tulisan ini bertujuan menganalisis dampak perubahan harga padi, jagung dan kedelai terhadap perdagangannya, serta implikasinya terhadap pendapatan usaha tani. Penetapan harga acuan pembelian (HAP) yang hanya mempertimbangkan biaya usaha tani untuk memproduksi padi, jagung dan kedelai belum memberikan dukungan yang optimal bagi upaya peningkatan pendapatan usaha tani pajale. Untuk itu, perlunya mempertimbangkan semua komponen biaya serta intervensi pemerintah dalam membantu memperkuat posisi tawar petani dalam sistem perdagangan ketiga komoditas tersebut di Indonesia sehingga rantai pasok dari petani ke tangan konsumen akhir dapat dipangkas dengan tujuan dapat memberikan implikasi secara langsung terhadap peningkatan pendapatan usaha tani.